PENGARUH PEMBERIAN EKSTRAK REBUNG BAMBU DAN LAMA PENYIMPANAN TERHADAP VIABILITAS BENIH BAWANG MERAH (Allium wakegi Araki) - Nurhayati, Fitri; Maemunah, Maemunah (Fakultas Pertanian, Universitas Tadulako, 2024)
This study examined the effects of bamboo shoot extract and storage duration on the viability of shallot seeds of Palu Valley variety. The experimental design was a factorial randomized block with two factors: bamboo shoot extract concentrations (10, 20, and 30 ml/liter of water) and seed storage durations (30, 40, 50, and 60 days). This resulted in twelve treatments, each replicated three times. Data were analyzed using analysis of variance, followed by an Honest Significant Difference test at the 5% level to compare treatment means. Results showed that bamboo shoot extract at 20 ml and 30 ml significantly increased the number of leaves in the first week and plant height in the first and second weeks. A 60-day storage duration positively affected germination, leaf number, plant height, and root volume.